Opportunistic bone density screening for the abdominal radiologist using colored CT images: a pilot retrospective study. - Smith, Andrew; Khan, Majid; Varney, Elliot; Liu, Boshen; Roda, Manohar; Reed, Chris; Morris, Robert; Joyner, David; Lirette, Seth T.; Mosley, Thomas (Abdominal Radiology, 2019)
Purpose: The purpose of the study was to develop an accurate and reproducible method for detecting low spinal bone density on abdominal CT images.Methods: For this IRB-approved HIPAA-compliant single-center retrospective study, nonenhanced CT images of the lower abdomen were obtained in 631 African-American participants. Mean attenuation of L3/L4 was associated with quantitative CT bone density (QCT) in a randomly selected training cohort (N = 511), and receiver operating characteristics analysis was used to identify the optimal mean attenuation threshold for differentiating normal from low bone density. Custom image processing software was used to generate grayscale and colored CT images of the midline spine, with green for normal and red for low bone density. Five radiologists independently assessed bone density at L3/L4 in a validation cohort (N = 120) using various methods: QCT, visual assessment of sagittal grayscale images (Grayscale), quantitative measurement of mean attenuation on a midline sagittal image (Attenuation), and visual assessment of a midline sagittal colored image (Color). Accuracy was calculated using the average QCT bone density as a reference standard. Inter-observer agreement was assessed using intraclass correlation coefficient (ICC).Results: The optimal mean attenuation threshold for differentiating normal from low bone density at L3/L4 was 145 Hounsfield Units. The average accuracy of Grayscale, Attenuation, and Color methods was 58, 87, and 91% (p < 0.001), respectively. Inter-observer agreement was poor for Grayscale (ICC: 0.20; 95% CI 0.12, 0.28) and excellent for both Attenuation (ICC: 0.85; 95% CI 0.73, 0.91) and Color methods (ICC: 0.87; 95% CI 0.83, 0.90).Conclusion: Detection of low spinal bone density using colored abdominal CT images was highly accurate and reproducible.